Representation of Remilitarization and Nationalism under Shinzo Abe’s Regime at ‘Kamen Rider Build Series’ - Hamdan Nafiatur Rosyida (KIRYOKU, 2023)
Through the television show Kamen Rider Build, Shinzo Abe, who was re-elected as prime minister of Japan for the term 2012–2020, attempted to reinterpret Article 9 of the Japanese Constitution. This study highlights the remilitarization and nationalism issue. This paragraph includes a demilitarization issue to do rid of the honor pacifist mentality that military troops adopted as a result of American pressure following Japan's humiliating defeat in World War II. Japan, which Abe ultimately labels an "abnormal country" since it lacks military troops, instead only possesses the Jietai/Japan Self Defense Force (JSDF) as a governmental security force. Abe builds on increased military power by increasing the military budget and relaxing the rules governing the JSDF through the reinterpretation of Article 9. This argument presents advantages and disadvantages, yet it backs right-wing politicians in the Liberal Democratic Party (LDP). The US-Japan alliance was strengthened as a result, although tensions in the East Asian region grew. Through symbols and other aspects that appear utilizing representation theory, this political issue is depicted in the television series Kamen Rider Build, which Toei developed in 2017. Through this, it is possible to see that the Kamen Rider Build series is an allegory of the dynamics of the remilitarization debate during Shinzo Abe's administration through popular culture and successful nationalism ideology propaganda media to the larger Japanese community. Keywords: Kamen Rider Build, Nationalism, Remilitarization, Shinzo Abe